Assessment of tissue development in fattening quails using the stable isotope technique - Rezende, J. C. R. [UNESP]; Sartori, M. M. P. [UNESP]; Sartori, J. R. [UNESP]; Ducatti, C. [UNESP]; Denadai, J. C. [UNESP]; Pezzato, A. C. [UNESP] (Wiley-Blackwell, 2017)
We aimed to study the behaviour of tissue renewal in blood, pectoral muscle and keel of fattening quails during their growth and adulthood through carbon-13 turnover using the stable isotope technique. Three hundred male European quails were randomly subjected to six treatments. Diets fed to animals were initially based on corn and soybean meal and were replaced at 0, 7, 14, 21, 28 and 35days of age with diets of rice grits and soybean meal. These diets have distinct isotopic signals and over time it changes; the tissue will incorporate dietary signal, and then, we can measure the return time for each tissue in each age. Treatments were T1 (0 to 21days), T2 (7 to 35days), T3 (14 to 42days), T4 (21 to 56days), T5 (28 to 63days) and T6 (35 to 70days). Carbon-13 turnover in tissues of the birds at the above-mentioned time periods was calculated using the first-order exponential function. The values of half-lives were 2.6, 3.6, 5.4, 6.3, 9.0 and 9.8days for blood and 2.0, 1.7, 4.8, 6.7, 6.9 and 6.6days for pectoral muscle in treatments T1, T2, T3, T4, T5 and T6 respectively. The half-lives for the keel in treatments T2, T3, T4, T5 and T6 were 2.0, 5.4, 7.7, 8.9 and 15days respectively. Thus, half-life in sampled tissues generally increased with age of birds. Initially, the tissue half-lives are influenced by growth, and at the end of the growth cycle, the breast muscle tissue was the most metabolically active in either periods, followed by blood and the keel. All tissues showed a sigmoidal growth curve, which can be confirmed by half-life as a function of age.
Keywords: body growth; half-life; quail farming; metabolism; stable isotopes